The Implementation of The British Council Website to Support Indonesian EFL Learners - Putri, Vika Rahayu; Franscy, Franscy (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2022)
This study aims to find out and understand the implementation of the British Council website and what the problems are. This research used qualitative approach with case study method involving 20 respondents (students) as the sample and 5 teachers from different schools. The sample selection of this research used Stratified Random Technique. Data collection techniques of this research included interview, observation, questionnaire, and documentation. The researchers used triangulation, member checking, and reflexivity to assess the research's trustworthiness. The result of the researcher's observation is that the British Council website can be used from all sides. Be it videos, audio, short stories, practice questions and so on. This is in accordance with the results of the questionnaire given by the students, as many as 11 of 20 students (55%) stated that the British Council website learning was very interesting. Policy recommendation proposed such as the school must provide more support and supporting facilities to teachers and students to continue using the web by providing sufficient quota facilities for teachers and other supports. With that, the use of the British council website can make it easier for teachers to carry out various online teaching and learning activities with students.